Salt Tolerance, Morphological and Anatomical Responses of in vitro Indigofera zollingeriana Miq. Seedling - Çiğdem Alev ÖZEL; Siti MAESAROH (ISPEC Journal of Agricultural Sciences, 2021)
The species belonging to genus Indigofera with high nutritional value and tolerance against abiotic stresses are widely distributed in the tropics to the subtropic areas world over. In this study, two years old stored seeds of I. zollingeriana, a potential forage used in Indonesia, were evaluated for their tolerance to salinity stress. In the first step, the morphology and anatomy of I. zollingeriana seedlings under in vitro salinity stress level of 20-120 mM NaCl were investigated after 14 days. In the second step, the 3 days old seedlings were transferred to several concentrations of NaCl (140-300 mM) to estimate Ld50 (lethal dose). Several concentrations of gibberalic acid (GA3) were applied to the previous estimated Ld50 (228 mM NaCl) medium for alleviating seedlings damage. It was estimated that the increasing concentration of NaCl caused reduction in the evaluated plant growth parameters and changed anatomy of the root and stem cross sections. The 100% mortality of the seedlings was noted after4 weeks on the medium containing 300 mM NaCl. Treatment of seedlings with  <0.25 mg L-1 GA3 +228 mM NaCl (Ld50)   in the culture medium was effective to  reduce root damage for 4 weeks.   Treatment of seedlings with >2.5 mg L-1 GA3 + 228 mM NaCl (Ld50) showed adverse effects in controlling damage by necrosis and blackening of roots and stems.